Slow Tech and ICT A Responsible, Sustainable and Ethical Approach - Patrignani, Norberto (Springer International Publishing, 2018)
This book makes an important contribution to the recent evolution in Information and Communication Technologies (ICT) that are human-centred and socially desirable, environmentally sustainable, and ethically acceptable. It introduces the concept of moral, equitable and environmental limits in the ICT domain and proposes a Slow Tech approach to face the challenges of these limits, laying out a set of principles that can be applied in real-life business settings. With the launch of the United Nations Sustainable Development Goals and the growing interest in the circular economy, Slow Tech and ICT - A Responsible, Sustainable and Ethical Approach is a timely tool for forward-thinking businesses.